Real Goods solar living sourcebook : your complete guide to living beyond the grid with renewable energy technologies and sustainable living - Schaeffer, John, 1949-; McKibben, Bill (Gabriola Island, BC, Canada : New Society Publishers, 2014)
What book would you want if you were stranded on a desert island? Widely regarded as the "bible" of off-grid living, Real Goods Solar Living Source Book might be your best choice. With over six hundred thousand copies in print worldwide, it is the most comprehensive resource available for anyone interested in lessening their environmental footprint or increasing their energy independence
Relocalization -- Land and shelter -- Sunshine to electricity -- From panel to plug -- Emergency preparedness and solar mobility -- Energy conservation -- Water development -- Water heating -- Water and air purification -- Composting toilets and greywater systems -- Regenerative homesteading and farming -- Urban homesteading -- Sustainable transportation -- Natural burial -- The Real Goods' sustainable living library
Includes bibliographical references and index
Keywords: Solar energy; Renewable energy sources